Functional analysis of miR-21-3p, miR-30b-5p and miR-150-5p shuttled by extracellular vesicles from diabetic subjects reveals their association with diabetic retinopathy - Mazzeo, Aurora; Lopatina, Tatiana; Gai, Chiara; Trento, Marina; Porta, Massimo; Beltramo, Elena (Experimental eye research, 2019)
Microvascular dysfunctions due to altered interactions between endothelial cells (ECs) and pericytes are key-events in the pathogenesis of diabetic retinopathy. Extracellular vesicles (EVs) derived from mesenchymal stem cells cultured in diabetic-like conditions enter pericytes, cause their detachment and migration, and stimulate angiogenesis. We recently showed that EVs from diabetic patients with retinopathy have different miRNA profiling patterns from healthy controls, and determine features of retinopathy in in vitro models of retinal microvasculature. In particular, a role for intra-vesicle miR-150-5p, miR-21-3p and miR-30b-5p was hypothesized. In this work, we further characterized EVs from subjects with diabetic retinopathy and investigated miR-150-5p, miR-21-3p and miR-30b-5p functions inside microvascular cells. Human retinal pericytes and ECs were transfected with mimics or inhibitors, as appropriate, of miR-21-3p, miR-30b-5p and miR-150-5p, to evaluate their ability in promoting cell migration and tube formation. mRNA and protein profiling of EVs extracted from diabetic subjects with (DR group) or without retinopathy (noDR group), and healthy controls (CTR group) were also performed. Modulation of miR-150-5p, miR-21-3p and miR-30b-5p inside microvascular cells confirmed their involvement in abnormal angiogenesis. mRNA analysis revealed differing expression of 7 genes involved in angiogenesis, while subsequent protein analysis confirmed increased expression of HIF-1α in DR group. Since all these molecules are involved in the hypoxia-induced retinal damage characteristic of the disease, our data reinforce the hypothesis of a potential use of miR-150-5p, miR-21-3p and miR-30b-5p extracted from circulating EVs as prognostic biomarkers for diabetic retinopathy. •Prognostic biomarkers for diabetic retinopathy are needed.•Functional studies confirm miR-150-5p, miR-21-3p, miR-30b-5p involvement.•HIF-1α is also increased in extracellular vesicles from diabetic retinopathy subjects.•miR-150-5p, miR-21-3p, miR-30b-5p and HIF-1α concur to hypoxia-induced angiogenesis.•Intra-vesicle miR-150-5p, miR-21-3p, miR-30b-5p as biomarkers of diabetic retinopathy.